English (One Health & Risk Management, 2023)
Introduction. Mortality among tuberculosis patients, both nationally and globally, has decreased significantly in the last 10 years, but the current epidemiological situation in tuberculosis allows to predict a new rise in the endemic state of the disease due to the increase of TB/HIV coinfection and the resistant tuberculosis. Material and methods. The patient’s reports were analyzed – new cases, deaths due to the progression of tuberculosis registered in the Municipal Clinical Hospital of Phthisiopneumology, Chisinau, in 2 periods: the 1st period – 2001-2003 and the 2nd period – 2018-2020. During both periods, 64 new cases died in the hospital due to the progression of tuberculosis. Statistical data processing was performed with the application of the Student (t) test, the data were considered statistically true when p